Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1523-1755.2000.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal denervation on the sodium excretory actions of leptin in hypertensive rats

Abstract: Collectively, these results are interpreted to suggest that the blunted natriuretic and diuretic responses to leptin observed in the SHR with intact renal nerves may be partially explained by the antinatriuretic effect of an enhanced baseline efferent renal sympathetic activity and/or leptin's stimulation of the sympathetic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
5
19
0
Order By: Relevance
“…Accordingly, the renal effects of leptin may not only be viewed as the result of plasma hormone level elevation, but also as highly dependent on the underlying regional and systemic hemodynamics, baseline sodium, and water balance. Numerous studies have demonstrated that acute administration of synthetic leptin in the rat produces a significant elevation in urinary sodium and water excretion [14,15,32,34]. Serradeil-Le et al [32] reported that in normal, hydrated, conscious rats intraperitoneal injections of synthetic murine leptin were associated with a significant two-to threefold increase in urinary volume.…”
Section: Leptin and The Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the renal effects of leptin may not only be viewed as the result of plasma hormone level elevation, but also as highly dependent on the underlying regional and systemic hemodynamics, baseline sodium, and water balance. Numerous studies have demonstrated that acute administration of synthetic leptin in the rat produces a significant elevation in urinary sodium and water excretion [14,15,32,34]. Serradeil-Le et al [32] reported that in normal, hydrated, conscious rats intraperitoneal injections of synthetic murine leptin were associated with a significant two-to threefold increase in urinary volume.…”
Section: Leptin and The Kidneymentioning
confidence: 99%
“…The latter hypothesis was examined by a study that evaluated the hemodynamic and renal excretory effects of leptin in anesthetized spontaneously hypertensive rats with either acute or chronic renal denervation [34]. In rats with acute renal denervation, an intravenous bolus of leptin produced a significant two-to fourfold elevation in sodium excretion.…”
Section: Leptin and The Kidneymentioning
confidence: 99%
“…Dietary-induced obesity is associated with a reduced expression of leptin receptors in the kidney in rats [72] and dogs [73]. Resistance to the natriuretic effect of leptin was observed in SHR [48] and renal denervation restored sensitivity to leptin [74], suggesting an important role of increased renal sympathetic activity. Increased renal SNA is commonly observed in obese animals and humans [75].…”
Section: Selective and Peripheral Leptin Resistancementioning
confidence: 99%
“…These effects are blunted in spontaneously hypertensive rats (SHR) with intact nerves [42,43]. This observation suggests that leptin-mediated stimulation of sympathetic nervous system counteracts the natriuretic effects under normal conditions [44]. An increased sympathetic nerve activity has been recently associated with progression of renal disease [45].…”
Section: Leptin and The Kidneymentioning
confidence: 99%